β2-Glycoprotein I Is Proteolytically Cleaved In Vivo upon Activation of Fibrinolysis - Horbach, Daniëlle A.; Oort, Erica van; Lisman, Ton; Meijers, Joost C. M.; Derksen, Ronald H. W. M.; de Groot, Philip G. (Thrombosis and Haemostasis, 1999)
β2-glycoprotein I (β2GPI) is a plasma glycoprotein with unknown physiological function(s). In in vitro experiments it has been demonstrated that β2GPI has both anticoagulant properties, such as the inhibition of factor X and prothrombin activation and procoagulant properties, such as the inhibition of the anticoagulant activity of activated protein C. Besides this, β2GPI bound to cardiolipin is recognized by anti-phospholipid antibodies (aPL).In this study we demonstrate that β2GPI is very sensitive for cleavage between Lys317 and Thr318 by plasmin, resulting in two immunologically different cleaved forms. In vitro experiments show that these plasmin cleaved forms of β2GPI bind to negatively charged phospho-lipids with much lower affinity compared to intact β2GPI. Similar to plasmin, trypsin and elastase can also induce this proteolytical cleavage in β2GPI, whereas thrombin and factor Xa do not cleave β2GPI. The in vivo occurrence of the proteolytical cleavage was demonstrated by the finding that in plasmas of patients with disseminated intravascular coagulation(DIC) and in plasmas of patients treated with streptokinase, significant amounts of cleaved β2GPI (up to 12 μg/ml) are present.During the development of DIC, the increase in levels of cleaved β2GPI is accompanied by a 70% decrease in the levels of intact β2GPI, whereas in streptokinase treated patients levels of intact β2GPI stay within the normal range.This study demonstrates for the first time that during in vivo activation of fibrinolysis β2GPI is cleaved, which results in the formation of a form of β2GPI with much lower affinity for negatively charged phospholipids. Plasmin is most likely responsible for this modification.